Strategi Penguatan Kebijakan Energi Biodiesel di Indonesia untuk Mewujudkan Prinsip Ketujuh SDGs - Aditya Wisnu Pradana; Anugerah Yuka Asmara; Agus Fanar Syukri (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The Indonesian government is enthusiastic about continuing the biodiesel program as one of the new and renewable energy mandatory programs which has proven to be able to provide many benefits ranging from achieving environmentally friendly energy, saving state foreign exchange, increasing energy security, to providing jobs; in line with the 7th principle of sustainable development goals (SDGs). In fact, the Indonesian government has increased the B30 Biodiesel program in 2020 to B35 in 2023. It is supported by the Palm Oil Plantation Fund Management Agency (BPDPKS), which has the authority to collect CPO export levy funds and redistribute them to biodiesel producers, so that they can produce biodiesel economically. With this mechanism, the Biodiesel program can be implemented even though the price of biodiesel is more expensive than fossil fuels, but does not burden the State Budget (APBN). However, this program is difficult to increase, because the availability of incentive funds is limited by the amount of CPO exported and the amount of the levy. The Ministry of Energy and Mineral Resources (ESDM) must find a way for the biodiesel energy program to achieve the 23% energy mix target in 2045, and not rely on export fund levies anymore.